Constructing the Tolerance in Interreligious Families for Making Peaceful and Harmony Life in Pancasila Village of Lamongan - Nasruddin, Nasruddin (Proceedings of International Conference on Da'wa and Communication, 2022)
This study examines peaceful and harmonious life through the construction of tolerance in interreligious families. So, the research focuses on how interreligious families construct tolerance to make making peaceful and harmonious life in Pancasila village of Lamongan. To answer the focus, this study uses qualitative research with a post-positivistic phenomenological approach and analyzes the data using Spreadly’s model. This study found that: (1) the interreligious families externalized the tolerance by utilizing their stocks of knowledge, previous experiences, and common sense of knowledge; (2) the interreligious families objectivize the tolerance by making public discourse and doing intersubjectively interpretation of tolerance. Then, they institutionalized and habituated the tolerance into their lives and surroundings. Afterwards, they traditionalized and passed the tolerance onto the next generation; and, iii) the interreligious families internalized the tolerance into themselves. However, in this process, they do not absorb the (existing) tolerance only but redefine, recontextualize and redefine it before re-externalizing tolerance.